PERCEPTION OF THE CHILDREN FROM 7 TO 12 YEARS ABOUT DRUGS IN LATIN AMERICA - Fernandes Moll, Marciana (2015)
Introduction. This article aims at analyzing the perception of children from 7 to 12 years on the subject of drugs, during the period 1992-2012. one of the most repetitive problems in child populations is the use of alcohol, tobacco and other drugs, whose exhibition starts at increasingly younger ages, reason for which the participation of teams from working together with parents, educators, psychologists, psychiatrists, social workers, public authorities, is essential to a global strategy of health promotion must join to confront the phenomenon of drugs in children.Methods.To collect information used various full articles indexed in LILACS and SCIELO recovering 54 articles, of which only ten had regarding the issue under study.Result. In none of the studies was established difference in perception between the children from aspects such as sex, age, family, social and economic conditions; However, relates countries, yes detected differences, although minimal, mainly in regard to the approach to the issue, which focuses on consumption itself and not on perceptions that build children in relation to consumption.Conclusion. The children perceived as inappropriate drug use both legal and illegal, as they produce multiple consequences, sometimes triggering alterations in health and physical appearance, poor school performance, impaired social and family relations.